Long COVID impacts: the voices and views of diverse Black and Latinx residents in Massachusetts - Linda Sprague Martinez; Nihaarika Sharma; Janice John; Tracy A. Battaglia; Benjamin P. Linas; Cheryl R. Clark; Linda B. Hudson; Rebecca Lobb; Gillian Betz; Shayne Orion Ojala O'Neill; Angelo Lima; Ross Doty; et al. (BMC, 2024)
Abstract Objective To understand how Long COVID is impacting the health and social conditions of the Black and Latinx communities. Background Emerging research on Long COVID has identified three distinct characteristics, including multi-organ damage, persistent symptoms, and post-hospitalization complications. Given Black and Latinx communities experienced significantly higher COVID rates in the first phase of the pandemic they may be disproportionately impacted by Long COVID. Methods Eleven focus groups were conducted in four languages with diverse Black and Latinx individuals (n = 99) experiencing prolonged symptoms of COVID-19 or caring for family members with prolonged COVID-19 symptoms. Data was analyzed thematically. Results Most participants in non-English language groups reported they were unfamiliar with the diagnosis of long COVID, despite experiencing symptoms. Long COVID impacts spanned financial and housing stability to physical and mental health impacts. Participants reported challenging encounters with health care providers, a lack of support managing symptoms and difficulty performing activities of daily living including work. Conclusions There is a need for multilingual, accessible information about Long COVID symptoms, improved outreach and healthcare delivery, and increased ease of enrollment in long-term disability and economic support programs.